A new species of Ramaria subg. Laeticolora from Meghalaya, India - Biswas, Pinky Rani; Dutta, Arun Kumar (Phytotaxa, 2024)
A new species of coralloid fungus from Meghalaya, India, Ramaria pseudovinosimaculans, belonging to the genus Ramaria subg. Laeticolora, is proposed based on taxonomy and phylogenetic studies of the internal transcribed spacer of the ribosomal DNA (nrITS) region. The morphological characteristics, together with molecular studies, confirmed that the species is a novel species. The species is characterized by a small to medium-sized, radially branched, white to yellowish white basidiomata with a base colour of light brown to violet red and greyish yellow elsewhere that turns brownish orange when bruised, a cylindrical to bacilliform basidiospore, basally clamped four-spored basidia, and clamped hyphae. An inclusive description, illustration, and comparison with morphologically similar and related species are provided.